DETERMINAN FEE AUDIT EKSTERNAL DALAM KONVERGENSI IFRS - Ulfasari, Hanifah Kurnia; Marsono, Marsono (Diponegoro Journal of Accounting, 2014)
This study aims to examine the determinant of external audit fees in IFRS convergence. Several factors expected to affect external audit fees determination are client’s complexity, client’s size, litigation risks, type of auditor, and auditor switching. These factors are expected to increase external audit fees. In addition, this study also linked the implementation of IFRS and auditing are still few in Indonesia.             This study is a modification of the study De George’s et al (2013). This study is modified by adding independent variables and used secondary data from non-financial companies which listed on Bursa Efek Indonesia (BEI) in 2011 and 2012. This study uses purposive sampling method and obtains sample of 128 companies. The effect of client’s complexity, client’s size, litigation risks, type of auditor, auditor switching and audit fees are tested using multiple linear regression analysis contained in SPSS 16.Before being conducted the regression test, it is examined by using the classical assumption tests.          The results of this study indicate that client’s complexity, client’s size, and, type of auditor have significant relationship on external audit fees. Whereas, litigation risks and auditor switching do not have significant relationship on external audit fees. This study also shows that type of auditor especially the Big Four played an important role after IFRS is applied in Indonesia.